(untitled) (Research, Society and Development, 2024)
The article aims to study public education policies for deaf students in Brazil, as well as the challenges of their inclusion in the school environment. Methodology: This is a qualitative bibliographical research. In Brazil, over the last few years, there have been significant advances in the field of research and production of materials to improve the conditions of deaf students in society and at school. On April 24, 2002, it was regulated by Decree No. 5,626 and, at the end of 2005, which determined the inclusion of Libras as a mandatory curricular subject in teacher training courses, at secondary and higher levels, and in speech therapy courses, represents a huge achievement for the Deaf community. The study showed that it is a living language, each country has its own language, it is not universal, when inclusion is promoted, it teaches students without distinction, it allows respect for the right to quality education even if it is different from other modalities, such a discussion begins to gain strength more recently, through some thinkers who begin to raise questions about the model determined by the legal frameworks.